Characterization and cloning of an 11S globulin with hemagglutination activity from Murraya paniculata - Singh, Anamika; Selvakumar, Purushotham; Saraswat, Akhilesh; P.S. Tomar, Prabhat; Mishra, Manisha; K. Singh, Pradhyumna; K. Sharma, Ashwani (Protein and Peptide Letters, 2015)
A 56 kDa protein having hemagglutination activity was purified and characterized from the Murraya paniculata seeds. The gel electrophoresis studies demonstrated that protein is primarily of two different subunits, molecular weight 35 and 21 kDa held together by disulfide-linkages and predominantly by secondary forces. The cloning and sequence analysis revealed that the protein exhibited a substantial sequence identity to seed storage 11S globulin family proteins. The sequence analysis of Murraya paniculata globulin (MPG) demonstrated higher and lower molecular weight polypeptides to be acidic (α) and basic (β) respectively. The sequence analysis further showed that it possesses a characteristic bi-cupin motif and a putative metal binding pocket. CD analysis revealed that the MPG was a β/α protein with a slightly higher content of the former. Conformational changes in protein have been studied by fluorescence spectrometry by using various chemical treatments. The results demonstrated that MPG belongs to 11S globulin family and exhibit's hemagglutination activity, which implicates it to be possessing lectin-like property.
Keywords: Cupin motif